The effects of vitamin C and E supplementation on heat shock protein 70 response of ovary and brain in heat-stressed quail - Şahin, Nurhan; Tuzcu, M.; Orhan, C.; Onderci, M.; Eroksuz, Y.; Şahin, Kazım (Taylor & Francis Ltd, 2009)
1. The effects of vitamin C (L-ascorbic acid) and vitamin E (-tocopherol acetate) supplementation on egg production and heat shock protein 70 (Hsp70) response of ovary and brain in the Japanese quail (Coturnix coturnix japonica) exposed to high ambient temperature were evaluated. 2. The birds (n = 540; 55 d old) were randomly assigned to 18 groups consisting of 3 replicates of 10 birds each in a 2 3 3 factorial arrangement of treatments. Birds were kept in wire cages in a temperature-controlled room at either 22C (thermo-neutral, TN) or 34C (heat stress, HS) for 8 h/d (09:00 to 17:00 h; until the end of the study) and fed on a basal diet or the basal diet supplemented with either three levels of vitamin C (0, 250 and 500 mg of L-ascorbic acid/kg of diet) or three levels of vitamin E (0, 250 and 500 mg of dl--tocopheryl acetate/kg of diet). 3. Feed intake and egg production were not affected by vitamin C and E supplementation under thermo-neutral conditions. However, feed intake and egg production were increased with the vitamin C or E supplementation either singly or in combination in heat-stressed quail. When vitamin was added, feed intake and egg production of quails under TN were different from those raised under HS. However, in the absence of supplemental vitamins, feed intake and egg production at TN and HS were no different. 4. Heat exposure increased serum corticosterone levels and Hsp70 expression. Serum corticosterone level was significantly decreased by vitamin C or E supplementation in HS groups for quail. Ovary and brain Hsp70 expression linearly decreased as dietary vitamin C or vitamin E supplementation increased in heat-stressed groups. However, Hsp70 expression of ovary and brain was not affected by vitamin C or E supplementation under thermo-neutral conditions. 5. The present study showed that a combination of dietary vitamin C (500 mg) and E supplementation (500 mg) may alleviate some heat stress effects of heat shock proteins of ovary and brain and egg production of Japanese quail.
Keywords: Ascorbic-Acid; Shock Proteins; Broiler-Chickens; Mineral Concentrations; Egg-Production; Performance; Expression; Restriction; Nutrients; Blood